HUKUM PERKAWINAN ISLAM DI RUANG DIGITAL: Bias Gender dalam Wacana Hukum Perkawinan di Instagram - Handayani, Yulmitra (Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2021)
This study departs from the widespread social media content created and distributed by conservative groups. One of the topics frequently addressed by this group is family law discourse, which includes instructions for selecting a mate, marriage advice, the fulfillment of rights and obligations in the family, and other topics related to relationships in domestic life. Using Foucault's discourse analysis approach, this article investigates the dominant narratives that portray family law. The data for this study was gathered by examining discourse on the Instagram platforms @nikahsyari.com, @nikahbarokah, and @yuknikah.syari. These platforms were selected based on their popularity—number of followers. This research finds that marriage content on those Instagram platforms reflects what I refer to as fiqh-oriented and gender bias. The vast number of followers divided into online premarital classes enables account managers to subtly support and spread their ideology while attracting as many members as possible to their online courses. As a result, this conservative teaching influences the religious views and practices of their members, particularly regarding marriage and gender relations in the household.Kajian ini berangkat dari maraknya kehadiran konten-konten di media sosial yang dibuat dan disebarkan oleh kelompok konservatif. Salah satu wacana yang sering diusung oleh kelompok ini adalah hukum perkawinan seperti petunjuk memilih jodoh, anjuran menikah, pemenuhan hak dan kewajiban dalam rumah tangga serta topik-topik lain seputar relasi dalam kehidupan rumah tangga. Tulisan ini bertujuan untuk membedah narasi-narasi dominan yang merepresentasikan hukum keluarga dengan pendekatan analisis wacana Foucault. Data penelitian ini didapatkan dengan cara menginvestigasi wacana dalam platform “@nikahsyari.com”, “@nikahbarokah”, dan “@yuknikah.syar_i”. Platform ini dipilih berdasarkan banyaknya pengikut. Penelusuran terhadap konten-konten pernikahan di Instagram ini merepresentasikan hukum perkawinan dengan berorientasi fikih dan bias gender. Jumlah pengikut yang terbilang ratusan hingga ribuan, yang terbagi kedalam kelas-kelas pranikah online, membuat pengelola akun memiliki kuasa atas pengiringan opini dan penyebaran ideologinya sekaligus menarik sebanyak-banyaknya member dalam kelas onlinenya. Konsekuensinya, ajaran konservatif ini mempengaruhi praktik keagamaan dan cara pandang para member terhadap perkawinan dan relasi gender dalam rumah tangga khususnya.